Getting to the heart of the matter: A diary study of swimmers` appraisals of organisational stressors - Didymus, F. F.; Fletcher, D. (Journal of Sports Sciences, 2012)
We explored sport performers` cognitive appraisals of organisational stressors. The relevant demands and transactional alternatives that athletes experience in relation to the situational properties were identified. Thirteen national standard swimmers completed semi-structured, interval-contingent daily diaries for a 28-day period. A combination of inductive and deductive content analysis was used to organise and analyse the diary entries with a focus on the following areas: organisational stressors, their underlying situational properties, and the swimmers` transactional alternatives. One hundred and thirty-one of the organisational stressors were appraised as threat, 41 as challenge, and 83 as harm/loss. Support was found for the majority of Lazarus and Folkman's (1984) situational properties with the only exception being temporal uncertainty. Imminence was associated with the greatest number of threat appraisals (47), novelty was associated with the greatest number of challenge appraisals (17), and duration was associated with the greatest number of harm/loss appraisals (22). It is concluded that appraisal plays a pivotal role in sport performers` experiences of their organisational environment. Swimmers` transactional alternatives are influenced by the situational properties of the stressors encountered.